Novel Specialty Optical Fibers and Applications - Hu, Dora Juanjuan; Humbert, Georges (2022)
Novel Specialty Optical Fibers and Applications focuses on the latest developments in specialty fiber technology and its applications. The aim of this reprint is to provide an overview of specialty optical fibers in terms of their technological developments and applications. Contributions include:1. Specialty fibers composed of special materials for new functionalities and applications in new spectral windows.2. Hollow-core fiber-based applications.3. Functionalized fibers.4. Structurally engineered fibers.5. Specialty fibers for distributed fiber sensors.6. Specialty fibers for communications.